A Case of Spontaneous Rupture of the Spleen - El Brahmi, Yasser; El Fahssi, Mohammed; Mohamed, Anajjar; Nsengiyumva, Prosper; Abdelkader, Ehirchiou; Ait Ali, Abdelmounaim (International Journal of Innovative Research in Medical Science, 2020)
We report a case of non traumatic spontaneous rupture of the spleen unknown aetiology, attended to emergency with feature of acute abdomen.